2014
DOI: 10.1186/2050-6511-15-57
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and safety issues of an accidental overdose of 2,000,000 IU of vitamin D3 in two nursing home patients: a case report

Abstract: BackgroundAdministration of intermittent high doses of vitamin D3 is increasingly used as a strategy for rapid normalization of low 25-hydroxyvitamin D (25(OH)D) blood concentrations in patients with vitamin D deficiency. Here, we describe the pharmacokinetics of an accidental single oral overdose of 2,000,000 IU of vitamin D3 in two elderly nursing home patients and discuss safety issues.Case presentationTwo patients, a Caucasian 90-year old man and a 95-year old woman, were monitored from 1 h up to 3 months … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 24 publications
0
7
0
2
Order By: Relevance
“…Inappropriate administration of vitamin D. A single dose of 2 000 000 IU of vitamin D was given in error to two nursing home residents [67], leading to a call to replace multiple use bottles with smaller single-unit dose formulations. At the other extreme of age, most premature infant formulas have high vitamin D levels, which, while safe for short durations, if prolonged feeding is undertaken can result in excessive levels of vitamin D (>100 nmol l -1 ) [68].…”
Section: Causes Of Vitamin D Toxicitymentioning
confidence: 99%
“…Inappropriate administration of vitamin D. A single dose of 2 000 000 IU of vitamin D was given in error to two nursing home residents [67], leading to a call to replace multiple use bottles with smaller single-unit dose formulations. At the other extreme of age, most premature infant formulas have high vitamin D levels, which, while safe for short durations, if prolonged feeding is undertaken can result in excessive levels of vitamin D (>100 nmol l -1 ) [68].…”
Section: Causes Of Vitamin D Toxicitymentioning
confidence: 99%
“…Although it has been reported that vitamin D toxicity might occur with dosages of ≥10,000 IU/day for an extended period [ 71 , 84 ], producing adverse effects like hypercalcemia, the level of vitamin D causing toxicity is unclear [ 71 , 100 ], and due to ethical reasons, no prospective studies have analyzed the effect of vitamin D intoxication in humans. Recently, an accidental overdose of 2,000,000 IU of vitamin D 3 in two elderly patients did not cause adverse effects and only elevated blood calcium levels slightly [ 101 ]. More importantly, adverse effects have only been reported at serum concentrations of 25(OH)D above 200 nmol/L, which would take daily dosages of 40,000 IU or more of vitamin D to achieve [ 84 ], and serum concentrations of 25(OH)D of <140 nmol/L have not been correlated with hypercalcemia.…”
Section: Toxicity and Hypercalcemiamentioning
confidence: 99%
“… One case report described that a single dose of 2,000,000 IU of vitamin D was given in error to two nursing home residents. 28 This suggests the need to regulate the availability of multiple use bottles with more conventional dose formulations in line with current IOM and other published guidelines. 7 Consideration of vitamin D toxicity or excess should be made in patients presenting with hypercalcemia or hypercalciuria.…”
Section: Discussionmentioning
confidence: 88%